Negative thermal quenching in Er/Yb codoped lead-free halide perovskite Cs3Bi2Cl9 - Fatima S.; Kachhap S.; Ganaie Z.N.; Johari P.; Mishra N.K.; Kumar K.; Singh S.K. (My University, 2025)
Lanthanide (Er, Yb) doped lead-free halide perovskites (Cs3Bi2Cl9) have been developed, which crystallise into an orthorhombic structure with a Pnma space group. The material shows both direct (3.06 eV) and indirect (2.96 eV) bandgap. Theoretical calculation using DFT also predicts a direct bandgap at the Г position (3.12 eV) and a low-lying indirect bandgap from the Г point to a point between Г and Z point (3.08 eV), which are in close match with the experimentally observed values. The optimised Er/Yb: Cs3Bi2Cl9 demonstrated an intense upconversion (UC) emission (λexc= 980 nm), which shows an unusual negative thermal quenching effect, where the intensities of both the red and the green emissions increased with temperature. This effect is attributed to the efficient energy transfer from the sensitiser Yb3+ ions to the activator Er3+ ions due to the negative thermal expansion (NTE) of the lattice and the removal of moisture from the sample after heating. This unique optical feature has been used for optical temperature sensing applications using the fluorescence intensity ratio method. The observed absolute and relative temperature sensitivities of Er/Yb: Cs3Bi2Cl9 are 1.07 % K−1 and 0.98 % K−1, respectively, which is reasonably good. This work provides new insights for designing optical temperature sensors using lead-free halide perovskites at high temperatures and exploration of more halides showing NTE. © 2024 Elsevier B.V.